Current Response in CaV1.3–/– Mouse Vestibular and Cochlear Hair Cells - Manca, Marco; Yen, Piece; Spaiardi, Paolo; Russo, Giancarlo; Giunta, Roberta; Johnson, Stuart L.; Marcotti, Walter; Masetto, Sergio (Frontiers in Neuroscience, 2021)
Signal transmission by sensory auditory and vestibular hair cells relies upon Ca2+-dependent exocytosis of glutamate. The Ca2+ current in mammalian inner ear hair cells is predominantly carried through CaV1.3 voltage-gated Ca2+ channels. Despite this, CaV1.3 deficient mice (CaV1.3–/–) are deaf but do not show any obvious vestibular phenotype. Here, we compared the Ca2+ current (ICa) in auditory and vestibular hair cells from wild-type and CaV1.3–/– mice, to assess whether differences in the size of the residual ICa could explain, at least in part, the two phenotypes. Using 5 mM extracellular Ca2+ and near-body temperature conditions, we investigated the cochlear primary sensory receptors inner hair cells (IHCs) and both type I and type II hair cells of the semicircular canals. We found that the residual ICa in both auditory and vestibular hair cells from CaV1.3–/– mice was less than 20% (12–19%, depending on the hair cell type and age investigated) compared to controls, indicating a comparable expression of CaV1.3 Ca2+ channels in both sensory organs. We also showed that, different from IHCs, type I and type II hair cells from CaV1.3–/– mice were able to acquire the adult-like K+ current profile in their basolateral membrane. Intercellular K+ accumulation was still present in CaV1.3–/– mice during IK,L activation, suggesting that the K+-based, non-exocytotic, afferent transmission is still functional in these mice. This non-vesicular mechanism might contribute to the apparent normal vestibular functions in CaV1.3–/– mice.